Soil-ecological conditions of the north taiga flat-mound bog, Western Siberia ... - Raudina, Tatiana V.; Istigechev, Georgyi I.; Loiko, Sergey V. (Zenodo, 2023)
Of particular interest in the north of Western Siberia are frozen flat-mound bogs. Being formed in a transitional climatic zone, on the southern front of the permafrost zone, these frozen peatlands may turn out to be highly reactive upon thawing and deliver high amounts of solutes to the hydrological network. A detailed study of a flat-mound bog was carried out in a key area of about 3 hectares (Purovsky district, Yamalo-Nenets Autonomous Okrug). The soil-ecological conditions of the site are described, as well as the effect of spatial heterogeneity on the composition and properties of soils. Using topographic mapping and photogrammetry, it was identified that the bog surface is characterized by distinct microtopography (mounds-hollows-thermokarst subsidence with a percentage areas ratio of 49:30:21, respectively). Small-scale variations in ecohydrological settings, microtopography, and vegetation affect the distribution of nutrients, organic carbon in soils, and DOC (dissolved organic carbon) in bog waters. ... : This work was supported by the Russian Science Foundation (project number 21-77-00021) ...